Divorce and Children Sexual Deviant Behavior from the Perspective of Criminal Law and Sustainable Development Goals - Fatin Hamamah; Vasavvi Acharjya; Didi Sukardi (Universitas Kuningan, 2025)
Divorce is a significant social phenomenon that affects the emotional and psychological development of children worldwide. Therefore, this study aims to (1) analyze the factors influencing children post-divorce sexual deviant behavior related to the International Sustainable Development Goals (SDG) policy, (2) examine the impact of divorce on children mental and emotional health, (3) explore the role of criminal law in protecting children from deviant behavior due to divorce, and (4) investigate solutions to reduce the negative impact of divorce on children. This study uses an empirical legal approach by analyzing a specific case in Cirebon, Indonesia. A qualitative method was also used, with data collected through in-depth interviews, legal document analysis, and case studies, contributing to a more comprehensive understanding of the problem. The results showed that divorce is a contributing factor to the emergence of sexual deviant behavior in children, mainly due to neglect, inadequate parental supervision, and exposure to a negative social environment. Furthermore, this study shows that the problem is exacerbated by an inadequate legal framework for child protection after divorce. The results contribute to SDG 3 Good Health and Well-being, SDG 5 Gender Equality, SDG 4 Quality Education, as well as SDG 16 Peace, Justice, and Strong Institutions by identifying the key factors influencing children's sexual deviant behavior after divorce. In conclusion, this study underscores the importance of implementing effective legal reforms and social programs to fulfill the needs of children affected by divorce. Policymakers and legal practitioners should foster international dialogue on enhancing children welfare and improving legal responses to divorce-related issues.